Validation of Evolving Software - Chockler, Hana.; Kroening, Daniel; Mariani, Leonardo; Sharygina, Natasha; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book describes the methodology and accompanying technology for reducing the costs of validation of changes by introducing automatic techniques to analyze and test software increments. It builds a unified approach to efficient and reliable validation of changes and upgrades, and may be used as a research monograph and a reference book.
Introduction -- Challenges of Existing Technology -- Static Analysis -- Dynamic Analysis -- Hybrid Analysis -- Quality of Validation.
Keywords: Software engineering; Computer logic; Software Engineering; Logics and Meanings of Programs